High temperature MBE of graphene on sapphire and hexagonal boron nitride flakes on sapphire - Cheng, Tin S.; Davies, Andrew; Summerfield, Alex; Cho, YongJin; Cebula, Izabela; Hill, Richard J.A.; Mellor, Christopher J.; Khlobystov, Andrei N.; Taniguchi, Takashi; Watanabe, Kenji; Beton, Peter H.; Foxon, C. Thomas; et al. (AIP, 2016)
The discovery of graphene and its remarkable electronic properties has provided scientists with a revolutionary material system for electronics and optoelectronics. Here, the authors investigate molecular beam epitaxy (MBE) as a growth method for graphene layers. The standard dual chamber GENxplor has been specially modified by Veeco to achieve growth temperatures of up to 1850 _C in ultrahigh vacuum conditions and is capable of growth on substrates of up to 3 in. in diameter. To calibrate the growth temperatures, the authors have formed graphene on the Si-face of SiC by heating wafers to temperatures up to 1400 _C and above. To demonstrate the scalability, the authors have formed graphene on SiC substrates with sizes ranging from 10 _ 10mm2 up to 3-in. in diameter. The authors have used a carbon sublimation source to grow graphene on sapphire at substrate temperatures between 1000 and 1650 _C (thermocouple temperatures). The quality of the graphene layers is significantly improved by growing on hexagonal boron nitride (h-BN) substrates. The authors observed a significant difference in the sticking coefficient of carbon on the surfaces of sapphire and h-BN flakes. Our atomic force microscopy measurements reveal the formation of an extended hexagonal moir_e pattern when our MBE layers of graphene on h-BN flakes are grown under optimum conditions. The authors attribute this moir_e pattern to the commensurate growth of crystalline graphene on h-BN.